2020
DOI: 10.1177/1524839920936241
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Health Among Young Men Who Have Sex With Men and Transgender Women With HIV: Lessons Learned From Implementing the weCare Intervention

Abstract: Young gay, bisexual, and other men who have sex with men and transgender women with HIV, particularly those who are racial or ethnic minorities, often have poor health outcomes. They also utilize a wide array of social media. Accordingly, we developed and implemented weCare, an mHealth (mobile health) intervention where cyberhealth educators utilize established social media platforms (e.g., Facebook, texting, and GPS-based mobile applications [“apps”]) designed for social and sexual networking) to improve HIV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 22 publications
0
38
0
2
Order By: Relevance
“…While participants reported some confusion about conflicting and emerging information related to COVID-19, they utilized multiple and credible sources to obtain information about the pandemic and risk reduction. This finding could reflect, in part, their past participation in the weCare intervention, which improves health literacy by helping participants identify, evaluate, and use online sources of health information, including CDC and HRSA websites [21,23,24]. Thus, despite our sample knowing quite a bit about COVID-19, many PLWH may need support in identifying and accessing correct and updated information to manage their health in light of the dissemination of conflicting information regarding COVID-19.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…While participants reported some confusion about conflicting and emerging information related to COVID-19, they utilized multiple and credible sources to obtain information about the pandemic and risk reduction. This finding could reflect, in part, their past participation in the weCare intervention, which improves health literacy by helping participants identify, evaluate, and use online sources of health information, including CDC and HRSA websites [21,23,24]. Thus, despite our sample knowing quite a bit about COVID-19, many PLWH may need support in identifying and accessing correct and updated information to manage their health in light of the dissemination of conflicting information regarding COVID-19.…”
Section: Discussionmentioning
confidence: 91%
“…In our research with GBMSM living with HIV in the U.S. South, we have found that most own or have access to smartphones; however, most do not have access to desktop computers or laptops at home. Thus, they may not have the requisite technology and/or a private place to participate in telemedicine visits that utilize a video component [21,23,24,27,28]. Transition to telemedicine could potentially reduce HIV care engagement and viral suppression and increase disparities among some of the most vulnerable populations living with HIV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LifeSkills Mobile is among the first mHealth interventions that have been developed to meet the specific and unique needs of YTW to reduce sexual risk for HIV acquisition and transmission. It joins other such mHealth initiatives, focusing on transgender women, which are in the development or testing phases [57][58][59][60].…”
Section: Principal Findingsmentioning
confidence: 99%